CO2 Activation by Lewis Pairs Generated Under Copper Catalysis Enables Difunctionalization of Imines - Li, Zhenghua; Zhang, Liang; Nishiura, Masayoshi; Luo, Gen; Luo, Yi; Hou, Zhaomin (Journal of the American Chemical Society, 2020)
Integration of distinct substrate activation modes in a catalytic circle is critical for the development of new, powerful synthetic methodologies toward complex and value-added chemicals from simple and readily available feedstocks. Here, we describe a highly selective difunctionalization of imines through incorporation of activation of CO2 by intramolecular N/B Lewis pairs into a copper catalytic cycle. Experimental and computational studies on the mechanistic aspect revealed an α-borylalkylamido intermediate, a metal amide-based Lewis pair formed by borylation of a C–N double bond, and enabled an unprecedented CO2 fixation pattern that is in sharp contrast to the traditional CO2 insertion into transition-metal-element bonds. The unique lithium cyclic boracarbamate products could be easily transformed into multifunctional N-carboxylated α-amino boronates. The highly diastereoselective reactions of chiral N-tert-butanesulfinyl aldimines were also achieved. We hope that our findings may inspire further development of selective multicomponent reactions by incorporation of Lewis pair chemistry into transition-metal catalysis.